2008
DOI: 10.1128/ec.00466-07
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Cascade Required for Regulation of Development and Secondary Metabolism in Neurospora crassa

Abstract: Mitogen-activated protein kinase (MAPK) signaling cascades are composed of MAPK kinase kinases (MAPKKKs), MAPK kinases (MAPKKs), and MAPKs. In this study, we characterize components of a MAPK cascade in Neurospora crassa (mik-1, MAPKKK; mek-1, MAPKK; and mak-1, MAPK) homologous to that controlling cell wall integrity in Saccharomyces cerevisiae. Growth of basal hyphae is significantly reduced in mik-1, mek-1, and mak-1 deletion mutants on solid medium. All three mutants formed short aerial hyphae and the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 60 publications
7
75
1
Order By: Relevance
“…Therefore, we focused further efforts on defining the MAK-1 pathway. MAK-1 was previously shown to be phosphorylated after treatment with a ␤-1,3 glucan inhibitor, aculeacin A (29), suggesting that the MAK-1 pathway functions in the cell wall stress response pathway in Neurospora, similar to Slt2 in S. cerevisiae (43). Slt2 is also activated in response to increased temperatures, which can destabilize the integrity of the cell wall (44).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we focused further efforts on defining the MAK-1 pathway. MAK-1 was previously shown to be phosphorylated after treatment with a ␤-1,3 glucan inhibitor, aculeacin A (29), suggesting that the MAK-1 pathway functions in the cell wall stress response pathway in Neurospora, similar to Slt2 in S. cerevisiae (43). Slt2 is also activated in response to increased temperatures, which can destabilize the integrity of the cell wall (44).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies of Neurospora, the phosphorylation state of MAK-1 and MAK-2 has been detected using an available phospho-specific antibody against the mammalian homologs p44 and p42 (29,42). As expected, using this antibody in Western blots, bands were observed corresponding to the predicted sizes for MAK-1 (46.8 kDa) and MAK-2 (40.8 kDa) that were absent in the ⌬mak-1 and ⌬mak-2 strains, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12,53,60 We also found that the A. alternata Slt2 is involved in regulating biosynthesis of secondary metabolites, because Dslt2 mutant accumulated lower levels of ACT toxin and melanin. 45 The levels of ACT toxin and melanin were restored in a strain that expresses a wild-type copy of AaSlt2.…”
Section: The Cell Wall Integrity-mediated Signaling Pathway In a Altmentioning
confidence: 84%